RECOVERY OF SCLERACTINIAN MORPHOLOGIC DIVERSITY DURING THE EARLY JURASSIC IN MENDOZA PROVINCE, ARGENTINA (Ameghiniana, 2017)
After a diversity peak during the Late Triassic, corals were severely affected by the end-Triassic extinction. The study of their recovery is fundamental for a better understanding of the ecological rearrangement undergone by Early Jurassic marine invertebrate faunas. In this contribution we analyze the morphologic recovery shown by scleractinians in southern Mendoza Province, which is the only place in the Neuquén Basin with marine outcrops spanning the Triassic/Jurassic boundary. A two-stage recovery pattern was recognized. During the first stage (Hettangian–Sinemurian) only solitary corals, most of them discoidal, could be found. After a hiatus encompassing the latest Early Sinemurian and the Late Sinemurian, the second stage (Pliensbachian) developed. A sharp increase in morphological diversity of solitary corals is then recorded, with discoidal, cupolate, patellate, turbinate, trochoid/turbinate, trochoid/ceratoid and maybe cylindrical morphologies. Additionally, colonial forms with low degree of corallite integration (phaceloid and cerioid colonies) appeared in the basin. The diversification trend hereby described provides useful insight regarding the scleractinian recovery after the end-Triassic mass extinction event within southern basins of South America. Furthermore, this recovery pattern is comparable with the one recognized for other regions (Chile, western North America, central Asia) yet it differs from that observed in some European basins. The trend outlined herein for Early Jurassic corals from the Neuquén Basin may reflect a large-scale phenomenon and/or the action of local adverse conditions (such as fluvial influence), which is open to further testing. Resumen. RECUPERACIÓN DE LA DIVERSIDAD MORFOLÓGICA DE LOS ESCLERACTINIOS DURANTE EL JURÁSICO TEMPRANO EN LA PROVINCIA DE MENDOZA, ARGENTINA. Después de un máximo de diversidad durante el Triásico Tardío, los corales se vieron severamente afectados por la extinción del final del Triásico. El estudio de su recuperación resulta fundamental para una adecuada comprensión del reacomodamiento ecológico de las faunas de invertebrados marinos del Jurásico Temprano. Se analiza aquí la recuperación morfológica experimentada por los escleractinios en el sur de la Provincia de Mendoza, único lugar en la Cuenca Neuquina con afloramientos marinos del pasaje Triásico–Jurásico. Se reconoce un patrón de recuperación de dos fases. Durante la primera fase (Hetangiano–Sinemuriano) sólo se registran corales solitarios, en su mayoría discoidales. Después de un hiato que abarcó la última parte del Sinemuriano Temprano y todo el Sinemuriano Tardío se desarrolló la segunda fase (Pliensbachiano). Se registra entonces un incremento marcado en la diversidad morfológica de los corales solitarios, con formas discoidales, cupulares, pateladas, turbinadas, trocoides/turbinadas, trocoides/ceratoides y posiblemente cilíndricas. Además, aparecen en la cuenca formas coloniales con bajo grado de integración de sus coralitos (faceloides y cerioides). La diversificación reconocida aporta información útil acerca de la recuperación de los escleractinios tras la extinción masiva de finales del Triásico en cuencas australes de Sudamérica. Este patrón de recuperación es comparable al de otras regiones (Chile, oeste de Norteamérica, Asia central) aunque difiere del hallado en algunas cuencas europeas. La tendencia aquí esbozada para los corales del Jurásico Temprano de la Cuenca Neuquina podría estar reflejando un fenómeno de gran escala y/o condiciones locales adversas (como influencia fluvial), lo cual plantea la posibilidad de futuros estudios.